2018
DOI: 10.1111/ecog.04093
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of ignoring spatial variation in population trend when conducting a power analysis

Abstract: Long-term, large-scale monitoring programs are becoming increasingly common to document status and trends of wild populations. A successful program for monitoring population trend hinges on the ability to detect the trend of interest. Power analyses are useful for quantifying the sample size needed for trend detection, given expected variation in the population. Four components of variation (within-year variation at a given site, interannual variation within a site, variation among sites in the interannual var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…; Weiser et al. ). Of course, there are perfectly sensible reasons why researchers may choose to begin work where their study organisms are abundant, and many inferences are not affected by such decisions—but estimates of population trends are.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Weiser et al. ). Of course, there are perfectly sensible reasons why researchers may choose to begin work where their study organisms are abundant, and many inferences are not affected by such decisions—but estimates of population trends are.…”
Section: Discussionmentioning
confidence: 99%
“…First, long-term studies should always report site selection criteria (for an analogous argument, see Coppolillo et al [2004]). Second, where possible, researchers should consider random sampling of available habitat as a means of choosing study populations or formally consider the spatial variability of population trends (Vos et al 2000;Yoccoz et al 2001;Weiser et al 2019). Of course, there are perfectly sensible reasons why researchers may choose to begin work where their study organisms are abundant, and many inferences are not affected by such decisions-but estimates of population trends are.…”
Section: Discussionmentioning
confidence: 99%
“…The panel of study areas or sites that are grouped for analysis needs careful consideration, with higher power likely to be achieved when grouped sites have similar responses (Weiser et al 2018). Our simulations assumed the same trend across the three study areas, an assumption that is unlikely to hold true, as areas probably experienced different fishing pressure before MPAs were established and likely experience different levels of recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hamilton et al (2010) showed that grouping areas biogeographically for MPAs around the Channel Islands, California, improved statistical power to detect trends. Alternatively, different trends can also be included in hierarchical models for multiple sites (e.g., Urquhart 2012, Perkins et al 2017), although power to detect overall trends may be low when trends among sites differ substantially (Weiser et al 2018). Further work exploring the influence of including a larger number of study areas with differing levels of response is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…First, long-term studies should always report site selection criteria (for an analogous argument, see Coppolillo et al (2004)). Second, where possible, researchers should consider random sampling of suitable habitat as a means of choosing study populations, or formally consider the spatial variability of population trends (Vos et al 2000;Yoccoz et al 2001, Weiser et al 2018. Of course, there are perfectly sensible reasons why researchers may choose to begin work where their study organisms are abundant, and many inferences are not affected by such decisions -but estimates of population trends are.…”
Section: Discussionmentioning
confidence: 99%